Influence of temperature climatology on productivity of Wheat crop in India - VENKATARAMAN, S.; RAHI, A. K. (MAUSAM, 1983)
The need for an examination of Rabi season temperature climatology in wheat crop productivity is mentioned. The optimum temperature requirements for various phases or wheat are indicated. The climatic constraints and agronomic strategy for maximal wheat crop production in each of the fourteen temperature based wheat zones are detailed.